PEMBELAJARAN MODEL REALISTIC MATHEMATICS EDUCATION (RME) PADA KEMAMPUAN PEMECAHAN MASALAH MATERI PECAHAN SISWA KELAS 3 SD - Suhada, Ira Irawati; Rabbani, Sylvia (IKIP Siliwangi, 2020)
This reaserch is a classroom action reaserch that aims to determine the effectiveness of the RME model and the result of the RME evaluation in learning mathematics in fraction material in grade 3 students of Sekolah Dasar Negeri 253 Panggungsari Bandung.Realistic mathematics learning begins with the real worlds, in order to facilitate students in learning mathematics, then students with the help of the teachers are given the opportunity to discover their own mathematical concepts. Existing procedures in applying the RME model are the preparation, opening, learning precess dan final stages. Evaluation of the RME model is seen from the activities of students based on aspects of verval activities and seeing students who are active and enthusiastic in participating in learning activities, do not interfere with friends when studying, dare to come to the front of the class and do assignment calmly and without haste.The result showed thet the application of the RME learning model to simple fractions material could increase student learning activities and outcomes. This can be seen from the pretest results of student who achieve mastery learning by 39.28% and an increase in postest result to 78.57%Keywords: Model, Realistic Mathematics Education (RME), Mathematical Fractions.Â